Global Overshoot Contemplating the World's Converging Problems - Cocks, Doug. (Springer New York : Imprint: Springer, 2013)
Global Overshoot isa multidisciplinary analysis (including history and pre-history) from an ecological and evolutionary perspective of the contemporary world system. This book compares and critiques attitudes held by people with different world views to the hypothetical prospect of large widespread falls in quality of life. It alsodraws insights from these two analyses to develop and suggest a philosophy of Ecohumanism to people of good will who want to think constructively about the worlds converging problems, i.e. think altruistically and think like an evolving ecosystem.